0277 Environmental exposure to nanoparticles in Sardinia, Italy: a pilot study of residential exposure nearby an industrial area and a military shooting range. (23rd June 2014) - Campagna, Marcello; Marcias, Gabriele; Angius, Natalia; Fabbri, Daniele; Noli, Marcello; Pili, Sergio; Pilia, Ilaria; Avataneo, Giuseppe; Cocco, Pierluigi
Abstract : Objectives: Objective of our pilot study was to explore the airborne ultrafine particle count in residential areas nearby industrial and military settings with reference to urban and rural areas. Method: We monitored airborne ultrafine (ranging 7nm - 10 microm) particles in residential areas nearby a large oil refinery, a military shooting range, in the largest urban area in the region and in a rural area. We conducted eight samplings (6 h each) using a Electrical low pressure impactor (ELPI plus - Dekati, Tampere, FInland). Wind speed and direction, temperature and humidity during each sampling were registered. Data on other potential sources of ultrafine particles, from both anthropic and natural origin, were also resigeterd. The airborne nanoparticle concentration was expressed as particle count/ cm 3 . Results: The median ultrafine particle count was 7408 (max 179605)/cm 3 in the residential area nearby the oil refinery, 9079 (max 114281)/cm 3 nearby the military shooting range, 19040 (max 142324)/cm 3 in the urban area and 25419 (max 373434) in the rural area. Conclusions: Our results show that ultrafine particles were ubiquitous in the sampling sites. Median counts were higher in the rural area than nearby industrial and military settings. We speculate that anthropic activities, including widespread use of wood burning fireplaces in rural areas, as well as technical measures to control industrial particulate emissions implemented in the past years, might have contributed. Further studies and additional sampling will allow a more detailed picture of exposure levels to better characterise risk of possible adverse health outcomes associated with environmental exposure to nanoparticles.